Left-Sided Portal Hypertension: A Case Series - Guntur Darmawan; Dinda Andini; Nenny Agustanty (The Indonesian Society for Digestive Endoscopy, 2018)
Left-sided portal hypertension is rarely found, but this condition may cause gastrointestinal tract bleeding and can be life-threatening. The exact incidence of left-sided portal hypertension is unknown as it is rarely found, approximately 1-5%, and most cases were misdiagnosed. We reported 3 cases of left-sided portal hypertension in male patient aged 34 years old, female patient aged 29 years old, and female patient aged 35 years old. Most diagnosis was made based on the clinical findings by excluding the diagnosis of cirrhotic portal hypertension. Splenic vein angiography remains the gold standard in diagnosing left sided portal hypertension. Left-sided portal hypertension is difficult to differentiate from cirrhotic portal hypertension because in these both abnormalities, varices can be present. Left-sided portal hypertension can be considered as a diagnosis in patient with upper gastrointestinal tract bleeding due to oesophageal varices, gastric varices, or portal hypertension gastropathy, accompanied with hypersplenism without the presence of hepatic abnormality or cirrhosis.